Standardization of β-Thromboglobulin (β-TG) and Platelet Factor 4 (PF4): A Collaborative Study to Establish International Standards for β-TG and PF4 - Kerry, P J; Curtis, A D (Thrombosis and Haemostasis, 1985)
An international collaborative study was carried out to determine the suitability of freeze-dried preparations of β-TG and PF4 to serve as international standards, and to compare these materials with other purified preparations and with plasma samples. Although problems remain with the accurate measurement of these proteins, it has been demonstrated that common standards improve the precision of measurement by RIA and provide an essential foundation for future work into the effects of assay system differences.The World Health Organization established in 1984 the purified preparation of β-TG (83/501) and the purified preparation of PF4 (83/505) as International Standards, with assigned potencies of 500 International Units per ampoule and 400 International Units per ampoule, respectively.
Keywords: β-thromboglobulin; Platelet factor 4; International Standards; Radioimmunoassay